Comparisons between cervical vertebrae and hand-wrist maturation for the assessment of skeletal maturity - (:unkn) unknown (My University, 1999)
It was claimed that, skeletal maturity could be determined by using anatomical changes of the cervical vertebrae observed on the lateral cephalometric radiographs. In this method of assessment cervical vertebrae C2, C3, and C4 are observed and each patient is placed in a cervical vertebrae maturation index (CVMI). Fishman developed a system of hand-wrist skeletal maturation indicators (SMI), using four stages of bone maturation at six anatomic sites. The purpose of this study was to analyze associations between cervical vertebrae maturation index (CVMI) and skeletal maturation index (SMI). The second objective was to determine the reproducibility of the identifications on the lateral cephalograms and hand-wrist films. Lateral cephalometric and left hand-wrist radiographs of 180 untreated subjects (99 girls and 81 boys) aged from 8 to 18 years were obtained from the files of the Marmara University School of Dentistry, Department of Orthodontics. The results of this study indicated that cervical vertebrae maturation and hand-wrist skeletal maturation were significantly related.
Keywords: Female; Humans; Adolescent; Male; Child; Cephalometry; Age Factors; Age Determination by Skeleton; Cervical Vertebrae; Maxillofacial Development; Hand; Bone Development; Carpal Bones; Radiation Dosage